Anthocyanin Extraction from Cockspur Coral (Erythrina crista-galli) Flowers Using a Microwave-Assisted Extraction (MAE) Method: Effect of Microwave Power and Feedstock-to-Solvent Ratio - Damayanti, Astrilia; Megawati, Megawati; Syafitri, Laila; Isaroyati, Luluk (International Journal of Research Innovation and Entrepreneurship, 2020)
Anthocyanin is a water-soluble compound as a coloring agent that can give rise colors in plants such as Cockspur Coral flowers. Cockspur Coral flowers contain antioxidants in the form of polyphenol compounds. This study investigated the effect of extraction time and the use of microwave power on anthocyanin concentrations in the microwave-assisted extraction (MAE). The use of MAE was beneficial due to its short extraction time, low need of solvent, and high yields of the target compounds. A 10 g of Cockspur Coral flowers was mixed with 4% of solvent containing citric acid and ethanol. The ratios of the feedstock to solvent were 1:5, 1:15, and 1:25. The extraction was done at various microwave powers of 300, 450, and 600 W with extraction times of 3-15 minutes. The results indicated that the extraction of Cockspur Coral flowers with a ratio of feedstock-to-solvent of 1:15 gave the highest total anthocyanin content at a microwave power of 600 W for 3 min. Whereas, the highest total phenolic (132.73 g/L) was reached at the extraction with a microwave power of 600 W for 12 min. The method of extraction of Cockspur Coral flowers using a MAE method did affect the total phenolics content. However, this method apparently did not show a significant effect on the total anthocyanin content.